KARAKTERISTIK KARBOKSIMETIL SELULOSA DARI ONGGOK SINGKONG PADA VARIASI KONSENTRASI NATRIUM HIDROKSIDA DAN ASAM TRIKLOROASETAT - Triasswari, Ni Putu Mega; Arnata, I Wayan; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): SeptemberDO - 10.24843/JRMA.2022.v10.i03.p07, 2022)
Onggok is tapioca solid waste that contains high cellulose but has not been used appropriately. This study aims to determine the concentration of NaOH and TCA to produce the best CMC characteristics of onggok. The study used a factorial randomized block design. The factor I was the concentration of NaOH (15%; 30%; and 45%), and factor II was the concentration of TCA (10%; 20%; and 30%). The variables observed included yield, water content, degree of substitution, NaCl content, and purity. The results showed that the concentration of NaOH and TCA significantly affected the yield, water content, degree of substitution, NaCl content, and purity of CMC. The concentrations of 45% NaOH and 30% TCA produced the best CMC characteristics with yield, moisture content, degree of substitution, viscosity, NaCl content, and CMC purity of 109.65±0.78%, 9.57±0.53%, 1.13±0.12, 170.00±10.00cPs, 0.86±0.40%, and 99.14±0.40%, respectively.